Media Portrayal of Female Celebrities in the Nigerian Press - Perpetua Ogechi Aondover; Eric Msughter Aondover; Olugbenga Charles Adewale; Omolara Oluwabusayo Akin-Odukoya; Lawal Umar Maradun (Budapest International Research and Critics University, 2024)
The media portrayal of female celebrities in the Nigerian press can be analyzed through several lenses, including representation, stereotyping, and societal expectations. The paper examined media portrayal of female celebrities in the Nigerian press and the postulation of Feminist Theory was employed to interrogate the concept. The paper argues that with the rise of social media, the portrayal of female celebrities has become more direct and personal. Celebrities now have more control over how they present themselves to the public, but they also face more intense scrutiny. Social media platforms can amplify both praise and criticism, sometimes leading to a toxic environment where female celebrities are constantly under the microscope, not only for their careers but also for their personal choices. Nigerian media coverage is often influenced by the country’s strong cultural and religious values. Female celebrities, especially in more conservative parts of the country, may face criticism for behavior that challenges traditional expectations of women. For example, the media may criticize women who dress in a revealing way, engage in public displays of affection, or speak out against societal norms. The portrayal of female celebrities in Nigerian media is complex and multifaceted, balancing between admiration and scrutiny, empowerment and objectification, personal choice and public expectation. The media plays a significant role in shaping public perceptions of female celebrities, both positively and negatively. The paper concludes that many female figures in entertainment, sports, and politics are portrayed as role models, especially when they defy norms and achieve success in male-dominated fields. Women like Genevieve Nnaji, Tiwa Savage, and Chimamanda Ngozi Adichie, for instance, are often celebrated for their professional achievements and contributions to society. This narrative promotes women's empowerment, independence, and leadership.